The genetic background of Parkinson's disease: current progress and future prospects. (12th February 2016) - Kalinderi, K.; Bostantjopoulou, S.; Fidani, L.
Abstract : Almost two decades of genetic research in Parkinson's disease (PD) have remarkably increased our knowledge regarding the genetic basis of PD with numerous genes and genetic loci having been found to cause familial PD or affect the risk for PD. Approximately 5–10% of PD patients have monogenic forms of the disease, exhibiting a classical Mendelian type of inheritance, however, the majority PD cases are sporadic, probably caused by a combination of genetic and environmental risk factors. Nowadays, six genes, a lpha synuclein, LRRK2, VPS35, Parkin, PINK1 and DJ‐1, have definitely been associated with an autosomal dominant or recessive PD mode of inheritance. The advent of genome‐wide association studies (GWAS) and the implementation of new technologies, like next generation sequencing (NGS) and exome sequencing has undoubtedly greatly aided the identification on novel risk variants for sporadic PD. In this review, we will summarize the current progress and future prospects in the field of PD genetics.